EKSISTENSI DAN FIGURITAS PEREMPUAN - Bannan Naelin Najihah; Naih Nurjanah (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This paper studies the method of interpretation of Muhyiddin Ahmad Mustafa Darwisy (1908-1982) concerning the verses of the existence and figure of women in the Qur’an in Surah Ali ‘Imran/3: 195 and al-Ahzab/33: 35. This study uses a descriptive qualitative method with a library research approach. The data analysis technique used content analysis of the text. The results of the study found that Darwisy’s interpretation covers three things, namely the source of interpretation, the method of interpretation, and the style of interpretation. Darwisy uses aspect of rationality as a source of interpretation, his method of interpretation is general in style (ijmaly), and his interpretation is linguistic in its pattern. The analysis also finds Darwisy’s role in the equal rights to adhere religion and to get education for women by using a language and literary approaches. The right to adhere religion in Darwisy thought coversguidance and rewards.